Isolation of Sulfate-Reducing Bacteria from Sediments Above the Deep-Subseafloor Aquifer - Fichtel, Katja; Mathes, Falko; Könneke, Martin; Cypionka, Heribert; Engelen, Bert (Frontiers in Microbiology, 2012)
On a global scale, crustal fluids fuel a large part of the deep-subseafloor biosphere by providing electron acceptors for microbial respiration. In this study, we examined bacterial cultures from sediments of the Juan de Fuca Ridge, Northeast Pacific (IODP Site U1301). The sediments comprise three distinctive compartments: an upper sulfate-containing zone, formed by bottom-seawater diffusion, a sulfate-depleted zone, and a second (∼140 m thick) sulfate-containing zone influenced by fluid diffusion from the basaltic aquifer. In order to identify and characterize sulfate-reducing bacteria, enrichment cultures from different sediment layers were set up, analyzed by molecular screening, and used for isolating pure cultures. The initial enrichments harbored specific communities of heterotrophic microorganisms. Strains affiliated to Desulfosporosinus lacus, Desulfotomaculum sp., and Desulfovibrio aespoeensis were isolated only from the top layers (1.3–9.1 meters below seafloor, mbsf), while several strains of Desulfovibrio indonesiensis and a relative of Desulfotignum balticum were obtained from near-basement sediments (240–262 mbsf). Physiological tests on three selected strains affiliated to Dv. aespoeensis, Dv. indonesiensis, and Desulfotignum balticum indicated that all reduce sulfate with a limited number of short-chain n-alcohols or fatty acids and were able to ferment either ethanol, pyruvate, or betaine. All three isolates shared the capacity of growing chemolithotrophically with H2 as sole electron donor. Strain P23, affiliating with Dv. indonesiensis, even grew autotrophically in the absence of any organic compounds. Thus, H2 might be an essential electron donor in the deep-subseafloor where the availability of organic substrates is limited. The isolation of non-sporeforming sulfate reducers from fluid-influenced layers indicates that they have survived the long-term burial as active populations even after the separation from the seafloor hundreds of meters above.